Assessment of Transport Specialists' Competencies in Transport/Logistics Companies. (2017) - Vaičiūtė, Kristina; Skirmantienė, Jolanta; Domanska, Lidia
Abstract: Constantly changing and globalized labour market is a new challenges for transport/logistics companies. Human resources become particularly important in organizations' competitive battle. Employees' knowledge and company's policies encompass essential resources of a company (skills, capabilities, employee potential). These essential resources are major advantages in a competitive battle. Therefore, employee's skills and competencies are one of the most important factors ensuring company's success in labour market. The research conducted in Lithuania and Poland enabled to identify strategic competencies of transport specialists.